Enhancing EFL Vocabulary Acquisition Through Gamification: Addressing Challenges and Boosting Retention - S. Nurfadilah, Auliyanti; Nur, Muh; Affandi, Akhmad (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2025)
Vocabulary acquisition is a fundamental aspect of mastering a foreign language, particularly for English as a Foreign Language (EFL) learners. However, many students face significant challenges in building their vocabulary, which hinders their ability to communicate effectively. Traditional teaching methods, such as L1 translation, memorization, and contextual guessing, are often inadequate, especially for beginners, as they fail to sustain long-term retention and engagement. This paper explores the limitations of these approaches and proposes the integration of games as an effective solution for vocabulary teaching. Games provide an engaging, interactive, and student-centered learning environment that fosters intrinsic motivation, encourages communication in real-life contexts, and reduces learner anxiety. The study highlights the benefits of using games to address the challenges in vocabulary acquisition, emphasizing their potential to create memorable learning experiences, enhance student participation, and promote sustained language development. By analyzing existing literature and the researchers’ teaching experience, this paper underscores the importance of innovative strategies to motivate EFL learners and improve their vocabulary acquisition.